2020
DOI: 10.3390/ijerph17165965
|View full text |Cite
|
Sign up to set email alerts
|

Community Pharmacist’s Role in Detecting Low Back Pain, and Patient Attitudes—A Cross-Sectional Observational Study in Italian Community Pharmacies

Abstract: Background: Low back pain (LBP) is one of the most frequent diseases for which patients seek advice in a community pharmacy. The study aimed to evaluate the feasibility of the administration by community pharmacists of questionnaires to assess the LBP intensity and disability degree in patients entering community pharmacies and the attitudes they have toward pain management by pharmacological and non-pharmacological strategies. Methods: An explorative, cross-sectional, observational, and quantitative study was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 34 publications
0
3
0
Order By: Relevance
“…Furthermore, patients with low and medium-intensity LBP are frequently seen by GPs or community pharmacists, putting community pharmacists in a unique position to collect and interpret health status data as well as provide advice to patients. 37 In recent years, community pharmacists have increased involvement in non-dispensing roles, 20 emphasizing the significance of this study since LBP is one of the most frequent musculoskeletal disorders reported by patients to CPs. 37 Unlike other studies on low back pain that concentrate on the pharmacists' knowledge of LBP and its treatments, this study primarily evaluates their attitudes, beliefs, and practices.…”
Section: Discussionmentioning
confidence: 92%
See 2 more Smart Citations
“…Furthermore, patients with low and medium-intensity LBP are frequently seen by GPs or community pharmacists, putting community pharmacists in a unique position to collect and interpret health status data as well as provide advice to patients. 37 In recent years, community pharmacists have increased involvement in non-dispensing roles, 20 emphasizing the significance of this study since LBP is one of the most frequent musculoskeletal disorders reported by patients to CPs. 37 Unlike other studies on low back pain that concentrate on the pharmacists' knowledge of LBP and its treatments, this study primarily evaluates their attitudes, beliefs, and practices.…”
Section: Discussionmentioning
confidence: 92%
“…37 In recent years, community pharmacists have increased involvement in non-dispensing roles, 20 emphasizing the significance of this study since LBP is one of the most frequent musculoskeletal disorders reported by patients to CPs. 37 Unlike other studies on low back pain that concentrate on the pharmacists' knowledge of LBP and its treatments, this study primarily evaluates their attitudes, beliefs, and practices. In this study, the majority of respondents were female, worked in independent pharmacies, had more than…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation